2016
DOI: 10.1038/ncomms11007
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting and rapid mobilization of endosteal HSC using a small molecule integrin antagonist

Abstract: The inherent disadvantages of using granulocyte colony-stimulating factor (G-CSF) for hematopoietic stem cell (HSC) mobilization have driven efforts to identify alternate strategies based on single doses of small molecules. Here, we show targeting α9β1/α4β1 integrins with a single dose of a small molecule antagonist (BOP (N-(benzenesulfonyl)-L-prolyl-L-O-(1-pyrrolidinylcarbonyl)tyrosine)) rapidly mobilizes long-term multi-lineage reconstituting HSC. Synergistic engraftment augmentation is observed when BOP is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 71 publications
5
46
0
Order By: Relevance
“…The dominant form of OPN in human and murine BM is thrombin-cleaved OPN (tcOPN), to which integrins a 4 b 1 and a 9 b 1 expressed on HSC can bind [Grassinger et al, 2009]. TcOPN has been demonstrated to be critical in the attraction, retention, and negative regulation of HSC proliferation and differentiation within the endosteal region [Nilsson et al, 2005;Stier et al, 2005;Grassinger et al, 2009] and recently we demonstrated that integrins a 4 b 1 and a 9 b 1 on HSC within the endosteal BM region are endogenously activated; and are therefore in a more ligand receptive state than their central BM counterpart [Cao et al, 2016a]. Moreover, as previously mentioned, tcOPN is produced locally within the BM, with megakaryocytes releasing all the required factors to cleave full length OPN [Storan et al, 2015].…”
Section: Extracellular Matrix Moleculesmentioning
confidence: 87%
See 2 more Smart Citations
“…The dominant form of OPN in human and murine BM is thrombin-cleaved OPN (tcOPN), to which integrins a 4 b 1 and a 9 b 1 expressed on HSC can bind [Grassinger et al, 2009]. TcOPN has been demonstrated to be critical in the attraction, retention, and negative regulation of HSC proliferation and differentiation within the endosteal region [Nilsson et al, 2005;Stier et al, 2005;Grassinger et al, 2009] and recently we demonstrated that integrins a 4 b 1 and a 9 b 1 on HSC within the endosteal BM region are endogenously activated; and are therefore in a more ligand receptive state than their central BM counterpart [Cao et al, 2016a]. Moreover, as previously mentioned, tcOPN is produced locally within the BM, with megakaryocytes releasing all the required factors to cleave full length OPN [Storan et al, 2015].…”
Section: Extracellular Matrix Moleculesmentioning
confidence: 87%
“…While calcium is the most recognized metal ion in the BM niche, magnesium and manganese ions have also been identified to be elevated in the endosteal region [Cao et al, ], which along with calcium, are known modulators of integrin activity [Pepinsky et al, ]. In particular, the greater calcium, magnesium and manganese content in the endosteal region has been shown to differentially prime/activate α 4 β 1 and α 9 β 1 integrins that are expressed by endosteal HSC [Cao et al, ] as demonstrated by binding of a divalent‐cation dependent α 4 β 1 /α 9 β 1 integrin probe [Cao et al, ].…”
Section: Non‐protein Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The small molecule N-(benzenesulfonyl)-l-prolyl-l-O-(1-pyrrolidinylcarbonyl)tyrosine (BOP), which is a dual ␣ 9 ␤ 1 /␣ 4 ␤ 1 integrin antagonist, mobilizes multilineage reconstituting HSPCs after a single dose in mice. 133 Administration of a single dose of BOP in combination with a single dose of AMD3100 mobilizes similar numbers of HSPCs as is observed after 4 days of G-CSF. However, in comparison with G-CSF, the combination of BOP and AMD3100 results in significantly enhanced short-and longterm engraftment in mice, indicating that this combination may be a rapid and effective alternative to G-CSF.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 74%
“…Furthermore, BIO5192 can be combined with G-CSF alone or with AMD31000 to increase levels of mobilized HSCs. BOP (N-(benzenesulfonyl)-L-prolyl-L-O-(1-pyrrolidinylcarbonyl)tyrosine), a small molecule targeting α9β1/α4β1 integrins also rapidly mobilizes long-term multi-lineage reconstituting HSC 10 . Synergistic engraftment augmentation is observed when BOP is co-administered with AMD3100.…”
Section: Introductionmentioning
confidence: 99%